Effect of Fuel Injection Timing on the Injection, Combustion, and Performance Characteristics of a Direct-Injection (DI) Diesel Engine Fueled with Canola Oil Methyl Ester-Diesel Fuel Blends - SAYIN, CENK; GÜMÜŞ, METİN (AMER CHEMICAL SOC, 2010)
In the last 3 decades, the search for alternative and renewable fuels, which have to be not only sustainable but also friendly with respect to the environment and techno-economically competitive, has gained importance because of the increasing environmental concerns and depletion in petroleum resources. Therefore, in this study, the influence of injection timing on the injection, combustion, and performance characteristics of a single-cylinder, four-stroke, direct-injection, naturally aspirated diesel engine has been experimentally investigated when using canola oil methyl ester (COME) and its blends with diesel fuel. The tests were conducted for three different injection timings [15 degrees, 20 degrees, and 25 degrees crank angle (CA) before top dead center (BTDC] at constant engine speed and different loads. The experimental test results showed that, because of the different properties of COME and diesel, both fuels exhibit different injection, combustion, and performance characteristics for different engine loads and injection timing. Investigation of injection characteristics of the fuels showed that using COME instead of diesel resulted in earlier injection timings. The maximum cylinder pressure, the maximum rate of pressure rise, and the maximum heat release rate are slightly lower, while the ignition timing is higher for COME and its blends for all loads and injection timings. The brake-specific fuel consumption for COME is higher than that of diesel fuel, while the brake thermal efficiency of COME is lower than that of diesel fuel. The original injection timing gave the best results for brake-specific fuel consumption, brake-specific energy consumption, and brake thermal efficiency compared to the advanced and retarded injection timings.
Keywords: COMPRESSION-IGNITION ENGINE; DELIVERY ADVANCE ANGLES; EXHAUST EMISSIONS; BIODIESEL FUEL; CI ENGINE; SEED OIL; PALM OIL; METHANOL; JATROPHA; KARANJA